1999
DOI: 10.1210/endo.140.6.6715
|View full text |Cite
|
Sign up to set email alerts
|

Anovulation in Cyclooxygenase-2-Deficient Mice Is Restored by Prostaglandin E2 and Interleukin-1β*

Abstract: Mice carrying a null mutation for either of the two cyclooxygenase (COX) isoenzymes, necessary for prostanoid production, exhibit several isotype-specific reproductive abnormalities. Mice deficient in COX-1 are fertile but have decreased pup viability, whereas mice deficient in COX-2 fail to ovulate and have abnormal implantation and decidualization responses. The present study identifies the specific contribution of each COX isoenzyme in hypothalamic, pituitary, and ovarian function and establishes the pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(86 citation statements)
references
References 56 publications
3
80
0
2
Order By: Relevance
“…Besides we studied COC expansion; another crucial process for oocyte development, ovulation, and fertilization [38][39][40]; and observed that cultured COCs, with LH?FSH and along with RU486, both setups showed normal COC expansion (Fig. 4b, c) as also revealed by previous studies [41][42][43][44]. Since cumulus cells do not express progesterone receptor (PR), COC expansion seems to be unaffected by RU486 (a PR antagonist).…”
Section: Discussionsupporting
confidence: 63%
“…Besides we studied COC expansion; another crucial process for oocyte development, ovulation, and fertilization [38][39][40]; and observed that cultured COCs, with LH?FSH and along with RU486, both setups showed normal COC expansion (Fig. 4b, c) as also revealed by previous studies [41][42][43][44]. Since cumulus cells do not express progesterone receptor (PR), COC expansion seems to be unaffected by RU486 (a PR antagonist).…”
Section: Discussionsupporting
confidence: 63%
“…Both mural granulosa and cumulus cells express high levels of COX-2 mRNA 4 h post-hCG in the mouse, with a second peak of COX-2 expression by cumulus cells at 12 h. LH is the principal determinant of COX-2 mRNA levels in mural granulosa cells (but not the COC) during the first peak of expression in ovulatory follicles. COX-2 mRNA levels in cumulus cells 12 h after hCG treatment are likely to be a function of factors derived from both the oocyte and the follicle wall, other than interleukin-1β (IL-1β) (Joyce et al 2001), which has previously been shown to restore ovulation in COX-2-deficient mice (Davis et al 1999). IL-1β stimulation also results in extensive leucocyte perifollicular infiltration in both COX-2 wild-type and null mice; however, in COX-2-deficient mice, this infiltration extends into the follicular antrum (Davis et al 1999), suggesting other COX-2-mediated roles in the follicle.…”
Section: Oocyte Ecm and Ovulationmentioning
confidence: 99%
“…The ovulation rate is reduced by COX‐2 suppression and this phenomenon can be inhibited by supplying prostaglandin E 2 or IL‐1 beta 13. However, it was unknown whether CINC/gro or COX‐2 took precedence in this process.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, COX‐2 is an inducible isoform that is responsive to many growth factors and to cytokine stimulation, especially to the factors that are produced during ovulation 11, 12. The ovulation rate is reduced by COX‐2 suppression13, 14 and this suppression can be inhibited by supplying prostaglandin E 2 or IL‐1 beta 13, 15…”
Section: Introductionmentioning
confidence: 99%